Hyperglycemia Recognized in Early Pregnancy Is Phenotypically Type 2 Diabetes Mellitus Not Gestational Diabetes Mellitus: A Case Control Study. Issue 3 (March 2021) - Agha-Jaffar, Rochan; Oliver, Nick S.; Kostoula, Melina; Godsland, Ian F.; Yu, Christina; Terry, Jayne; Johnston, Desmond; Gable, David; Robinson, Stephen
Abstract : (Abstracted from J Matern Fetal Neonatal Med 2020;33:3977–3983) Gestational diabetes mellitus (GDM) is defined as diabetes in pregnancy during the second or third trimester that is not overtly preexisting diabetes mellitus (DM). The time frame during gestation is based on the Hyperglycemia and Adverse Pregnancy Outcomes (HAPO) study, which showed an association between glucose and infants born large for gestational age in women who took a 75-g oral glucose tolerance test (OGTT) at routine testing (24–48 weeks' gestation).